Crumbs complex-directed apical membrane dynamics in epithelial cell ingression. - Simões, S.; Lerchbaumer, G.; Pellikka, M.; Giannatou, P.; Lam, T.; Kim, D.; Yu, J.; Ter Stal, D.; Al Kakouni, K.; Fernandez-Gonzalez, R.; Tepass, U. (Journal of Cell Biology, 2022)
Epithelial cells often leave their tissue context and ingress to form new cell types or acquire migratory ability to move to distant sites during development and tumor progression. Cells lose their apical membrane and epithelial adherens junctions during ingression. However, how factors that organize apical-basal polarity contribute to ingression is unknown. Here, we show that the dynamic regulation of the apical Crumbs polarity complex is crucial for normal neural stem cell ingression. Crumbs endocytosis and recycling allow ingression to occur in a normal timeframe. During early ingression, Crumbs and its complex partner the RhoGEF Cysts support myosin and apical constriction to ensure robust ingression dynamics. During late ingression, the E3-ubiquitin ligase Neuralized facilitates the disassembly of the Crumbs complex and the rapid endocytic removal of the apical cell domain. Our findings reveal a mechanism integrating cell fate, apical polarity, endocytosis, vesicle trafficking, and actomyosin contractility to promote cell ingression, a fundamental morphogenetic process observed in animal development and cancer.